Comparison between high‐resolution water‐perfused anorectal manometry and THD® Anopress anal manometry: a prospective observational study. (21st February 2020) - Leo, C. A.; Cavazzoni, E.; Leeuwenburgh, M. M. N.; Thomas, G. P.; Dennis, A.; Bassett, P.; Hodgkinson, J. D.; Warusavitarne, J.; Murphy, J.; Vaizey, C. J.
Abstract: Aim: Anorectal physiology tests provide a functional assessment of the anal canal. The aim of this study was to compare the results generated by standard high‐resolution water‐perfused manometry (WPM) with the newer THD ® Anopress manometry system. Method: This was a prospective observational study. Conventional manometry was carried out using a water‐perfused catheter with high‐resolution manometry and compared with the Anopress system with air‐filled catheters. All patients underwent the two procedures successively in a randomized order. Time to arrive at the resting pressure plateau, resting, squeeze, straining pressure and visual analogue scale (VAS) scores for pain were recorded. A qualitative analysis of the two devices was performed. Results: Between 2016 and 2017, 60 patients were recruited. The time from insertion of the catheter to arriving at the resting pressure plateau was significantly lower with the Anopress compared with WPM: 12 s [interquartile range (IQR) 10–17 s] versus 100 s (IQR 67–121 s) ( P  < 0.001). A strong correlation between the manometric values of WPM and the Anopress was observed. Both procedures were well tolerated, although the VAS score for insertion of the WPM catheter was significantly higher. The Anopress was easier to use and more time‐efficient than the WPM. Conclusion: The pressure values obtained with Anopress correlated well with those of conventional manometry. The Anopress has the advantage of being less time‐consuming, user‐friendly and better tolerated by patients.